Psychosis screening in schools: Considerations and implementation strategies. Issue 1 (9th July 2019) - Meyer, Monet S.; Rosenthal, Adi; Bolden, Khalima A.; Loewy, Rachel L.; Savill, Mark; Shim, Ruth; Rodriguez, Jacqueline; Flores, Victoria; Pavao, Earl; Niendam, Tara A.
Abstract: Aim: Duration of untreated psychosis, or the time between onset of psychosis symptoms and accurate diagnosis and treatment, is a significant predictor of both initial treatment response and long‐term outcomes. As such, efforts to improve rapid identification are key. Because early signs of psychosis commonly emerge in adolescence, schools have the potential to play an important role in the identification of psychosis‐spectrum disorders. Methods: To illustrate the potential role of schools in this effort, the current paper describes implementation of a psychosis screening tool as part of a larger study focused on reducing the duration of untreated psychosis in Sacramento, CA. Results: Clinical considerations related to screening for psychosis in schools, including ethical concerns, logistics, screening population and stigma are addressed. Implementation strategies to address these concerns are suggested. Conclusions: Early psychosis screening in the school system could improve early identification, reduce stigma and may represent an important further step towards an integrative system of mental health.